The role of obedience pressure and self-monitoring in public procurement fraud: An experimental analysis - Marundha, Amor; Herianti, Eva; Anggraini, Dahlia Tri (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2024)
Fraud in public procurement is a critical issue; it erodes public trust and disrupts service delivery. Understanding the factors behind procurement fraud is vital for creating effective prevention strategies. While previous studies have linked obedience pressure to unethical behavior, they have not fully examined the role of self-monitoring. This study addresses this gap by investigating the impact of obedience pressure on fraudulent procurement behaviors, with self-monitoring as a moderating factor. Using an experimental method and a 2x2 factorial design, the study involved accounting students from the University of Muhammadiyah Jakarta. Findings indicate that self-monitoring significantly influences the relationship between obedience pressure and fraud: high self-monitoring individuals do not reduce fraudulent behavior under obedience pressure, unlike their low self-monitoring counterparts. Conversely, highly self-monitoring individuals exhibit less fraud when not under obedience pressure compared to those who experience such pressure. The study concludes that regardless of self-monitoring levels, subordinates tend to follow superior orders, underscoring the need for strict supervision to curb unethical practices. This research enhances attribution theory by highlighting that obedience pressure from superiors is a key factor driving fraud in the procurement process.